Social-Ecologic Oriented Curricula in Engineering Education: “Leonardo’s Oath” as an Answer to Janus-Headedness in Engineering Work - R. Dreher; V. V. Kondratyev; M. N. Kuznetsova (Высшее образование в России)
Any engineering activity is characterized by contradictions: social – between engineering problems and technical solutions and technological – between laws of nature and artificial engineering objects. This leads to the ethical dilemma of engineering work: when creating something new, social and environmental problems usually arise. This explains the “Janus-headedness” of the engineering profession: although the original intention is to do good, however, there are negative consequences that must be mitigated through new technical solutions that have the effect of creating improvements. “Leonardo’s oath” not only highlights this need, but also serves as a reference point for developing the engineering training programs which should be prepared specifically for this task. As a starting approach, the article suggests using the “sustainability triangle” – a model of social transformational effects in relation to the definition of the variables “social”, “economy” and “ecology” and their corresponding interdependence. It is shown that digitalization changes the “economy” setting in the sustainability triangle, which inevitably leads to consequences for the currently dependent variables “social “ and “ecology”. Digitalization requires, first, an economic approach, not environmental. It does not solve the fundamental problem: participation in the formation of a society to achieve socio-ecological balance is faced with the duality between the ethical necessity of forming and lack of real balance.